WLE/Alliance leadership of a multi-stakeholder platform secretariat prompted dairy giants to join the zero-deforestation movement in Colombia - CGIAR Research Program on Water, Land and Ecosystems (2020)
The Alliance was asked to lead the multi-stakeholder platform technical Secretariat for Colombia’s zero-deforestation dairy value chain agreement. Alliance staff and partners went on an outreach blitz to encourage the sector’s big players to sign the agreement. With active engagement and support provided by the Secretariat, Alpina, a large corporation, and Asoleche, the national association of milk processors, signed the agreement within a year.